Perception of Factoring Transaction Risk by Bank - Szturo, Marek; Włodarczyk, Bogdan (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
Taking into account the sensitivity of modern banks to the growth of banking risk, we can observe a specific escape towards alternative financial services and the associated risk. The research presents the following research problems: “Does the factoring transaction allow for mitigation the transaction risk by the bank?”, “Are there phenomena on the Polish market of factoring services that may suggest a preferential approach of banks to the risk of factoring in the context of corporate clients?”. The article is a summary of the preliminary stage of research about the risk of factoring transactions in banking activity. The aim of the study was to assess the perception of the risk of a factoring transaction by the bank in the context of selected statistics of the factoring market in Poland. The research used the method of literature analysis, the method of comparisons over time of selected data from the factoring market statistics and the method of induction in the matter of inference and determination of further directions of research. Alternative financial services, which include factoring, thanks to the flexible form and diversification as well as the possibility of being excluded from the balance sheets, are becoming an increasingly attractive form, in particular short‑term financing of the bank’s corporate clients.